2004
DOI: 10.1083/jcb.200307056
|View full text |Cite
|
Sign up to set email alerts
|

FoxO3a regulates erythroid differentiation and induces BTG1, an activator of protein arginine methyl transferase 1

Abstract: Erythropoiesis requires tight control of expansion, maturation, and survival of erythroid progenitors. Because activation of phosphatidylinositol-3-kinase (PI3K) is required for erythropoietin/stem cell factor–induced expansion of erythroid progenitors, we examined the role of the PI3K-controlled Forkhead box, class O (FoxO) subfamily of Forkhead transcription factors. FoxO3a expression and nuclear accumulation increased during erythroid differentiation, whereas untimely induction of FoxO3a activity accelerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
132
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 159 publications
(138 citation statements)
references
References 51 publications
3
132
0
Order By: Relevance
“…Recently it has been shown that FOXO3a can play a role in erythroid differentiation through up-regulation of the B-cell translocation gene 1 protein (38). Bakker et al demonstrated that B-cell translocation gene 1 can modulate protein arginine methylation activity, which they propose is a novel mechanism regulating erythroid differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently it has been shown that FOXO3a can play a role in erythroid differentiation through up-regulation of the B-cell translocation gene 1 protein (38). Bakker et al demonstrated that B-cell translocation gene 1 can modulate protein arginine methylation activity, which they propose is a novel mechanism regulating erythroid differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The Id transcriptional repressors have been suggested to act at the checkpoint at which undifferentiated progenitor cells make the commitment to terminal differentiation. Id1 expression is high in proliferating, undifferentiated cells, whereas its expression is down-regulated as cells differentiate (38,49,50). For example, ectopic expression of Id1 inhibits B-cell development and differentiation of muscle and mammary epithelial cells (42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that BTG2 is induced by NGF, FGF, IL-6, TPA, serum, EGF, and cAMP (Bradbury et al, 1991;Fletcher et al, 1991;Montagnoli et al, 1996) indicating that a number of stimuli triggering different transduction pathways can activate the transcription of this gene. Also Btg1 has been shown to be a direct target of different molecules, including T3 hormone (Rodier et al, 1999), Insuline-like Growth Factor 1 (IGF-1) (Vadgama et al, 2006), or FoxO3A (Bakker et al, 2004). These data, together with the wide distribution and cell types where these genes are expressed during development, suggest that their regulation is likely to be dependent on cell type and cellular context.…”
Section: Discussionmentioning
confidence: 99%